Unlocking the potential of rice straw: Sustainable utilization strategies for Bangladesh - Bidhan Nath; Md Moudud Ahmmed; Subrata Paul; Md Durrul Huda; Mohammad Afzal Hossain; Sharmin Islam (Circular Economy)
Bangladesh annually produces vast amounts of rice straw. However, they have low utilization efficiency, with a significant portion being wasted, and are usually openly burned (cooking food/heating) by farmers, lost during collection, and discarded or directly burned in the field. Straw holds immense potential for conversion into valuable products beyond its raw form. In the 2021–2022 season alone, Bangladesh produced 52.25 million tons of rice straw, with an energy potential of 189.52 × 109 MJ. This study provided tangible information on various aspects of rice straw, including its availability, distribution, energy potential, common uses, and causes and impact as waste. Moreover, it is a comparative analysis of traditional uses alongside recent innovation utilization of straw. Suggested management options incorporating multifaceted conversion strategies are explored to encourage alternative utilization, which requires policies and diverse initiatives with financial support. Innovative approaches, such as the conversion of straw to renewable energy, along with alternative application strategies, are highlighted as promising technologies that can enhance flexibility and efficiency in utilization. Moreover, a comparative analysis has been carried out on traditional straw uses alongside recent innovations in its utilization, such as biogas production, biofuel generation, biochar creation, and composting, alongside value-added applications such as papermaking and industrial materials. A strategic approach to overcoming challenges and leveraging opportunities in rice straw utilization through technological advancements is proposed, aiming for sustainable and environmentally friendly practices. The current study emphasizes the importance of further research, particularly in the exploration of industrial and commercial applications of rice straw, to maximize its potential as a valuable agricultural residue.